Administrative decisions contingent upon the availability of financial allocation: A comparative analytical study - حسين, مصطفى رسول; محمد, گۆران ابراهيم (Sulaimani Journal for Humanities, 2019)
The General Administration is in the process of exercising its function may issue pending decisions on a standing condition resulting in the non-entry into force only if this condition is met, it may issue general organizational decisions on employees, such as the development of degrees of property and the salary of the salaries of those grades, Because the first-time employees or employees whose conditions have been modified under these regulations as their salary increases become entitlement even if there is no budgetary provision for these conditions. The administration may also issue individual decisions on individual or group of individuals who are nomads The State Treasury bears new burdens such as the decision to appoint a person or upgrade to a higher level of employment. The importance of this research is demonstrated by the effect of this type of administrative decision on the State treasury and on the rights of individuals in general and employees in particular.